ComplexSim: a flexible simulation platform for complex systems. (1st January 2013) - Messina, Fabrizio; Pappalardo, Giuseppe; Santoro, Corrado
This paper describes ComplexSim, a C-based simulation platform intended to support the study of P2P systems and complex networks. Its architecture is based on two layers: 1) the parallel simulation kernel, which manages the execution of simulations on SMP systems, by providing a clean API enabling the definition and scheduling of tasks and events; 2) the complex network data and runtime, which allows a complex network to be defined as a graph of entities endowed with user-defined attributes and runtime behaviour. This paper describes the design of ComplexSim as well as the API it provides. Moreover, some experimental results are reported, showing that, even in the case of huge complex networks with hundred million nodes, ComplexSim exhibits better performances, in terms of memory consumption and processing times, with respect to similar solutions.